Early Outcomes of Low Postoperative Bleeding after Off-Pump Coronary Artery Bypass Grafting - Weitie Wang; Yong Wang; Hulin Piao; Bo Li; Tiance Wang; Dan Li; Zhicheng Zhu; Rihao Xu; Kexiang Liu (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To investigate whether low bleeding influences the early outcomes after off-pump coronary artery bypass grafting (CABG). Methods: Retrospective analysis of ischemic heart disease patients who underwent off-pump CABG from January 2013 to December 2017. Patients were divided into low-bleeding group (n=659) and bleeding group (n=270), according to total drainage from chest tube during the first postoperative 12 hours. Clinical material and early outcomes were compared between the groups. Results: Baseline was similar in the two groups. Operation time was 270±51 min in the low-bleeding group and 235±46 min in the bleeding group (P<0.0001). The low-bleeding group presented smaller drainage during the first 12 h (237±47 ml) and shorter mechanical ventilation time (6.86±3.78 h) than the bleeding group (557±169 ml and 10.66±5.19 h, respectively) (P<0.0001). Hemodynamic status was more stable in the low-bleeding group (P<0.0001) and usage rate of more than two vasoactive agents in this group was lower than in the bleeding group (P<0.0001). Number of distal anastomosis, reoperation for bleeding, suddenly increase in chest tube output, intensive care unit (ICU) stay, hospital stay, and other early outcomes had no statistical significance between the groups (P>0.05). Conclusion: Postoperative bleeding < 300 ml/12 h in off-pump CABG patients did not require blood product transfusion and reoperation and that would contribute to reduction in mechanical ventilation time and maintaining hemodynamic stability. Bleeding < 800 ml during the first postoperative 12 h did not increase infection rates and ICU length of stay.